The use of Busuu Application to Improve Students? Vocabulary Mastery - Sri Lestari; Qori Aliarahmi; Lastry Forsia (Foremost Journal, 2025)
The aim of this research was to know whether there is a significant effect of Busuu application at the seventh grade students. This research was quasi experiment and was conducted by using quantitative method, 72 students as the sample which is divided into 36 students in the experimental class and 36 students in the control class. The sample taken nonrandom by purposive sampling. The research data was collected through pre-test and post-test as main data and observation as supporting data. The hypotheses data was tested using formula of t-test. It means there is significant effect used Busuu application to improve students? vocabulary mastery at the seventh grade students because the condition of students in experimental class are active and had many opinions during the learning. Besides that they more easily to improve students? vocabulary mastery by using Busuu application than control class only taught by used conventional method.